2009
DOI: 10.1002/jat.1446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acetaminophen (paracetamol) in the embryonic development of zebrafish, Danio rerio

Abstract: Acetaminophen, or paracetamol is an over-the-counter analgesic generally used by all groups of people, including pregnant women. The present investigation aims to elucidate the effects of acetaminophen on the development of zebrafish Danio rerio in which embryogenesis is ex utero. Developing eggs (n = 30) were exposed to different doses (0, 1, 5, 10, 50 and 100 microg L(-1)) of the drug in triplicate and observations were made hourly until gastrulation and once in 24 h thereafter for seven consecutive days. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 28 publications
6
42
1
Order By: Relevance
“…However, the effect of paracetamol seem to differ from the generic effect of common drugs on the pigmentation of fish. In fact, the here‐obtained data are similar to those obtained by David and Pancharatna (2009), who showed that environmentally relevant concentrations of paracetamol during the embryonic development of D. rerio , could result in changes namely, (lack) of pigmentation …”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of paracetamol seem to differ from the generic effect of common drugs on the pigmentation of fish. In fact, the here‐obtained data are similar to those obtained by David and Pancharatna (2009), who showed that environmentally relevant concentrations of paracetamol during the embryonic development of D. rerio , could result in changes namely, (lack) of pigmentation …”
Section: Discussionmentioning
confidence: 99%
“…While two of them, ethanol [25] and lindane [26], are widely considered to be neurotoxins at high dose, three are candidate neurotoxins: acetaminophen [27], [28], atenolol [29] and atrazine [30], [31], [32]. The last one, mefenamic acid, is considered to be neuroprotectant [33].…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen has also been previously tested in zebrafish and its general effect on embryonic development, nephrotoxicity and hepatotoxicity have been reported [27], [40], [41] but its neurotoxicity has not been studied. Its direct neurotoxic action has been recently established by both in vitro and in vivo studies in rats and neuronal apoptosis has been observed at concentration of 1–2 mM (150–300 mg/L) [28] Apparently the zebrafish larvae are more sensitive to acetaminophen as significant embryonic developmental defects were observed at concentration of 10 mg/L while significant shortening of axon length occurred at concentration as low as 2 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Other PAHs, such as benzo[a]pyrene and retene, are known to undergo hepatic metabolism [24], [25], [26], and exposure results in developmental malformations, including edemas and craniofacial malformations, in the developing zebrafish [27], [28], [29]. Certain pharmaceuticals, including acetaminophen and flutamide, are known to result in human hepatotoxicity [30], [31], [32], and can result in developmental toxicity in the zebrafish model [33].…”
Section: Introductionmentioning
confidence: 99%